Implementasi Pendidikan Karakter Dalam Upaya Pembinaan Perilaku Sosial Siswa - Kamaluddin Kamaluddin (Universitas Negeri Makassar, 2020)
This study aims to determine the implementation of character education in MTs Jeneponto, and the implementation of character education in efforts to foster social behavior in MTs Jeneponto. This research is descriptive qualitative, which is a process of collecting data systematically and intensively to obtain knowledge and information. In collecting data the researchers conducted in-depth observations and interviews by observing and interacting with the school principal, deputy headmaster for student affairs, social studies teachers and students of MTsN 1 Jeneponto, then looking for data by reviewing and evaluating documents and images that support the documentation. The study found that (1) The process of implementing character education in shaping the social attitudes of students in MTs N 1 Jeneponto was carried out by integrating character education into Integrated Social Studies learning so that character values could be embedded in students. in integrating such learning Integrated IPS teachers insert it into the RPP with the habituation of the teacher to students. (2) the implications of character education in the efforts to foster social attitudes through assessments conducted by teachers in K13 by looking at the dimensions of student attitudes.